Synthesis and Study Behavior of Some New Pyridinium Salts as Corrosion Inhibitors for Mild Steel in 1M H2SO4 - Abdu l-Raheem, Amro; S. Shihab, Mehdi (Al-Nahrain Journal of Science, 2022)
Some new pyridinium bromide derivatives inhibitors, namely; 1-benzyl-4-N-[(4-hydroxyphenyl) methylidene] hydrazinecarbonyl) pyridine-1-ium bromide, A1; 1-benzyl-4-N-[(4-ethoxyphenyl) methylidene] hydrazine carbonyl pyridine-1-ium bromide, A2; 1-benzyl-4-N-[(4-propoxyphenyl) methylidene] hydrazinecarbo-nyl pyridine-1-ium bromide, A3; were synthesized and studied as inhibitors corrosion for meld steel in 1M H2SO4 solution at room temperature via loss of weight measure ements for 24 hours. The results showed that inhibition for all pyridineum bromide derivatives have high values with the high concentrate. Increase in inhibition concentrate with corrosion rate decreases, inhibitor increasing and surface coverage degree increases. The free energy value of revealed physisorption effects for (A1, A2, and A3) and gave useful information to predict the interaction nature between the surface of metal and the organic molecules as corrosion inhibitors.